2001
DOI: 10.1046/j.1440-1746.2001.02459.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced colonization of gastric mucosa by Helicobacter pylori in mice deficient in interleukin‐101

Abstract: Our studies suggest that endogenous IL-10 is an inhibitor of the protective immune response to H. pylori infection. Interleukin-10 participates in the downregulation of H. pylori-induced gastric inflammatory responses, which apparently confers a survival advantage to the organism promoting more effective colonization of gastric mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 35 publications
4
50
0
Order By: Relevance
“…Several observations suggested the H. pylori-induced immune response is actively downregulated (20) (21). Our study provides evidence that the normal course of events during H. pylori infection involves suppression of the host anti-H. pylori response.…”
Section: Discussionsupporting
confidence: 55%
“…Several observations suggested the H. pylori-induced immune response is actively downregulated (20) (21). Our study provides evidence that the normal course of events during H. pylori infection involves suppression of the host anti-H. pylori response.…”
Section: Discussionsupporting
confidence: 55%
“…This shifts the Th1/Th2 immune balance, and the immunosuppressive nature of these cells can lead to tolerance against tumor Ags or pathogens (43,44). IL-10 2/2 mice, compared with wild-type mice, develop severe gastritis when infected with H. pylori bacteria; therefore, IL-10 may have a potential role in downregulating H. pylori-induced inflammation at the site of infection (45). However, we did not use H. pylori bacteria to stimulate DCs, but only HP-NAP, and did not observe IL-10 secretion from NAPDC, when cultured in the presence of tumor cell supernatant during the maturation process.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported significantly reduced colonization of the gastric mucosa in IL-10-deficient mice so that IL-10 seemed to be an inhibitor of the protective immune response to H. pylori infection (6). Thus, a role of Th1 type response may be important in the pathogenesis of H. pylori-associated disease.…”
Section: Discussionmentioning
confidence: 99%